2023
DOI: 10.3389/frsc.2023.1171996
|View full text |Cite
|
Sign up to set email alerts
|

Delivering sustainable, resilient and liveable cities via transformed governance

Christopher D. F. Rogers,
Nick Grayson,
Jonathan P. Sadler
et al.

Abstract: In the context of steadily declining Natural Capital and universal recognition of the imperative to reverse this trend before we get to the point that nature is not able to restore itself, cities have a crucial role to play. The UK Government commissioned a comprehensive study into the value of biodiversity, and by extension nature, reinforcing “why we should change our ways”—yet what is missing is the “how?”. This paper uniquely describes both the “how?” and a conclusive demonstration of the remarkable benefi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“…In line with Rogers et al (2023), we found that urban transformations do not just depend on policies and strategies, but on the willingness of key urban stakeholders to be agile and adjust to changing contexts and emerging technologies. Both case study cities were seeking to take advantage of smart city technologies to achieve their sustainability goals, particularly in waste management reforms.…”
Section: Benefits Of Agile Governance Practices and Entrepreneurshipsupporting
confidence: 72%
See 2 more Smart Citations
“…In line with Rogers et al (2023), we found that urban transformations do not just depend on policies and strategies, but on the willingness of key urban stakeholders to be agile and adjust to changing contexts and emerging technologies. Both case study cities were seeking to take advantage of smart city technologies to achieve their sustainability goals, particularly in waste management reforms.…”
Section: Benefits Of Agile Governance Practices and Entrepreneurshipsupporting
confidence: 72%
“…Our research uses a "transformative urban governance" conceptual model, drawing from the literature on urban sustainability transformations and urban transformative capacities (Wolfram, 2016(Wolfram, , 2019Borgström, 2019;Hölscher et al, 2019a;Hölscher and Frantzeskaki, 2021;Rogers et al, 2023). Transformative governance and decision-making in the context of urban sustainability transformations aim to re-direct urban development pathways toward sustainability and resilience (Fazey et al, 2017;Hölscher et al, 2019a).…”
Section: Conceptual Model-transformative Urban Governancementioning
confidence: 99%
See 1 more Smart Citation